Pengantar sejarah Indonesia Baru - Sartono Kartodirjo (Gramedia Pustaka Utama, 1992)
ast jil.2 =c.1/ ast jil.1 =c.1-4/ir, jil1=c.5/oen jil.1=c.6/ast, jil.2 =c.1/jil.1 =c.5/en, jil.2=c.2-3/en, jil.1=c.6/en, jil.2=c.10/jil.1, c.7